Control of root pathogens on onion seedling nursaries. - Navarro, Juan Ramón (2016)
The effect of several treatments to control root pathogens on onion seedlings (Allium cepa L.) were studied. The test was carried out in Bagaces, Guanacaste province, Costa Rica. Treat-ments tested were: Benomil + Captan, solarization for three weeks ,solarization for four weeks , compost at arate of 25 t/ha, and a control. During the test weather conditions were exceptionally wet thus increasing the pathogen pressure beyond normal. Despite weather conditions, the compost treatment showed the highest plant survival and seedlings. The use of compost seems to be an adequate altemative for the production of onion seedlings.